An ANALYSIS OF ONLINE MARKETING STRATEGIES THROUGH SOCIAL MEDIA FOR MSMES AFFECTED BY COVID-19 IN OKU DISTRICT: Online Marketing Strategies - Angga Wibowo Gultom; Rani Anwar; Titie Syahnaz Natalia (Enrichment : Journal of Management, 2021)
This study aims to analyze online marketing strategies through social media used by MSMEs in OKU Regency affected by COVID-19. The type of research used in this research is descriptive qualitative. The population in this study is MSMEs in OKU Regency. The sampling technique used purposive sampling as many as 120 samples. Interviews and documentation are data collection techniques used in this study. Researchers use data reduction methods (data reduction) in analyzing the data. This study shows that there are two kinds of online marketing strategies used, namely free and paid online marketing strategies. The results of this study indicate that the online marketing strategy through social media contributes positively to the increase in turnover. The highest increase in turnover is a strategy that uses paid social media features. Keywords: Strategy, Online Marketing, Social Media, MSMEs